The Impact of Influencer Marketing on Brand Loyalty and Credibility: The Mediating Role of Parasocial Interaction (Quest Journal of Management and Social Sciences, 2025)
Background: Advertisements that integrate influencer marketing have the potential to foster positive parasocial relationships with the target audience, eliciting a favorable emotional response from customers.Purpose: This study aims to investigate the impact of marketing on brand loyalty and credibility, taking into account parasocial interaction among users.Design/methodology/approach: This study employed an explanatory research approach to evaluate the attributes of influencers that influence consumer loyalty and credibility in the Kathmandu Valley, using the means-end chain model. Convenience sampling is employed in this study as a non-probability sampling technique. Data were collected from 429 respondents using structured questions administered through the KOBO toolbox. Following data collection, the data were analyzed using both descriptive and inferential statistics. The inferential analysis was conducted through structural equation modeling within SmartPLS 4.0.Findings: Findings reveal that Language Similarity and Interaction Frequency have a direct and significant impact on brand loyalty and credibility, with parasocial interaction serving as a mediating factor. The major challenges were identified as a gap between what is promised and what is delivered, and a lack of creativity, which can be minimized by realistic advertisements that showcase actual features and benefits.Conclusion: The study concludes that language similarity and frequent interactions play a critical role in strengthening brand loyalty and credibility, with parasocial interaction serving as an effective mediating mechanism. However, the industry still faces challenges, particularly the mismatch between promised and delivered value, as well as a lack of creative communication. Addressing these issues through authentic, realistic advertisements that highlight genuine features and benefits can significantly enhance consumer trust and long-term brand relationships.Keywords: Influencer Marketing, Brand Loyalty, Credibility, Parasocial Interaction, PLS SEM, Trust, Kathmandu Valley